The The Influence of The Electronic Word of Mouth (E-Wom) Dimension in Instagram on Purchasing Decisions At Kedai Ice Kepal in Mataram - Asmawati, Asmawati; Ridho, M. Zainul; Amrullah, Amrullah (Sumber Belajar Sejahtera, 2024)
This study aimed at assessing the impact of Electronic Word of Mouth aspects on purchasing decisions at Kedai Ice Kepal. The study utilized purposive sampling in collecting data. The sample size for this study consisted of 100 participants who were active users of Instagram platform and had previously followed the @Ice_Kepal_Mataram Instagram account and made a purchase at the Kedai Ice Kepal. According to the finding, at a significance level of 5%, the intensity dimensions have a favorable impact on purchase decisions. However, this impact is not statistically significant, as indicated by a significant value of 0.933, which is bigger than the threshold of 0.05. The content dimension has a favorable effect on purchase decisions, although this effect is not statistically significant. This is supported by the significance value of 0.103, which is bigger than the threshold of 0.05. The positive valence dimension exerts a positive and statistically significant impact on purchasing decisions, as indicated by a significant value of 0.000, which is below the threshold of 0.05. The negative valence dimension has a favorable effect on purchase decisions, although this effect is not statistically significant. This is supported by a significant value of 0.813, which is bigger than the threshold of 0.05. The test findings for the coefficient of determination (R2) indicate a value of 0.435, which corresponds to 43.5%. The independent variable has a 43.5% impact on the dependent variable, whereas the remaining portion is influenced by other variables that were not considered in this study.